Clinical Pattern of Tolvaptan-Associated Liver Injury in Subjects with Autosomal Dominant Polycystic Kidney Disease: Analysis of Clinical Trials Database - Watkins, Paul B.; Lewis, James H.; Kaplowitz, Neil; Alpers, David H.; Blais, Jaime D.; Smotzer, Dan M.; Krasa, Holly; Ouyang, John; Torres, Vicente E.; Czerwiec, Frank S.; Zimmer, Christopher A. (Drug safety, 2015)
Introduction Subjects with autosomal dominant polycystic kidney disease (ADPKD) who were taking tolvaptan experienced aminotransferase elevations more frequently than those on placebo in the TEMPO 3:4 (Tolvaptan Efficacy and Safety in Management of Autosomal Dominant Polycystic Kidney Disease and its Outcomes) clinical trial. Methods An independent, blinded, expert Hepatic Adjudication Committee re-examined data from TEMPO 3:4 and its open-label extension TEMPO 4:4, as well as from long-term (>14 months) non-ADPKD tolvaptan trials, using the 5-point Drug-Induced Liver Injury Network classification. Results In TEMPO 3:4, 1445 subjects were randomized 2:1 (tolvaptan vs. placebo) and 1441 had post-baseline assessments of hepatic injury. Sixteen patients on tolvaptan and one on placebo had significant aminotransferase elevations judged to be at least probably related to study drug. No association with dose or systemic exposure was found. Two of 957 subjects taking tolvaptan (0.2 %) and zero of 484 taking placebo met the definition of a Hy’s Law case. One additional Hy’s Law case was identified in a TEMPO 4:4 subject who had received placebo in the lead study. The onset of a hepatocellular injury occurred between 3 and 18 months after starting tolvaptan, with gradual resolution over the subsequent 1–4 months. None of the events were associated with liver failure or chronic liver injury/dysfunction. No imbalance in hepatic events was observed between tolvaptan and placebo in lower-dose clinical trials of patients with hyponatremia, heart failure, or cirrhosis. Conclusions Although hepatocellular injury following long-term tolvaptan treatment in ADPKD subjects was infrequent and reversible, the potential for serious irreversible injury exists. Regular monitoring of transaminase levels is warranted in this patient population.